Autoethnography as an Accessible Method of Research - Patrycja Polczyk (University of Lower Silesia, 2012)
Reflecting on my own experiences as a researcher with a disability who lives and works in Poland, I examine methodological issues critical to conducting qualitative research. I argue that autoethnography is a viable method for researchers who must overcome physical and/or cultural obstacles associated with a disability. I also maintain that autoethnography as well as its usefulness as a research method is inherently situated within the sociocultural conditions in which research is being conducted. Concluding, I imply that further studies are necessary for people with disabilities to re-gain voice and articulate their experiences.